Amelioration of junctional epidermolysis bullosa due to exon skipping. (6th March 2016) - Kowalewski, C.; Bremer, J.; Gostynski, A.; Wertheim‐Tysarowska, K.; Wozniak, K.; Bal, J.; Jonkman, M.F.; Pasmooij, A.M.G.
Summary: Mutations in the COL17A1 gene lead to the genetic blistering disorder junctional epidermolysis bullosa generalized intermediate type (JEB‐gen‐intermed). Antisense oligonucleotide‐mediated exon skipping is a strategy that aims to skip the mutation‐containing exon and thereby produce a smaller but functional protein. COL17A1 is an interesting candidate, as 53 of the 55 exons (96%) can be skipped without disturbing the reading frame. Information on the functionality of the shortened protein product is important in order to obtain support for this therapeutic strategy. Here we report a patient with JEB‐gen‐intermed with amelioration of the phenotype due to exon 49 skipping by two distinct mechanisms – premature termination codon‐induced exon skipping and revertant mosaicism – both of which induced skipping of the same exon. The patient was compound heterozygous for two inherited COL17A1 mutations, a frameshift mutation in exon 18 (c.1490_1491delinsT, p.Ala497Valfs*23) and a nonsense mutation in exon 49 (c.3487G>T, p.Glu1163Ter). Upon clinical examination, skin patches were found that were resistant to blister formation. In these patches, naturally corrected cells were present that harboured an additional splice‐site mutation, c.3419–1G>T, resulting in skipping of the mutation‐containing exon 49. This natural gene therapy phenomenon shows that type XVII collagen with residues 1140–1169 deleted is largely functional. In addition, in affected skin cells a low level of exon 49 skipping was observed. Our results support the notion that skipping of a mutated in‐frame exon in COL17A1 ameliorates the phenotype. Abstract : What's already known about this topic? Revertant mosaicism is a naturally occurring event that relies on the spontaneous correction of a pathogenic mutation. Antisense oligonucleotide‐mediated exon skipping is a new gene therapy that is under investigation for the treatment of epidermolysis bullosa. What does this study add? We identified a patient with junctional epidermolysis bullosa with two correction mechanisms both leading to in‐frame skipping of the mutated exon 49 in the COL17A1 gene – (i) premature termination codon‐induced exon skipping and (ii) correction of the inherited mutation by a spontaneous somatic splice‐site mutation. Our data support the use of antisense oligonucleotide‐mediated exon skipping as a therapeutic approach for epidermolysis bullosa.